Pn‐Heterojunction Diodes with n‐Type In2O3. (16th March 2015) - von Wenckstern, Holger; Splith, Daniel; Lanzinger, Stefan; Schmidt, Florian; Müller, Stefan; Schlupp, Peter; Karsthof, Robert; Grundmann, Marius
<x xml:space="preserve">Abstract</x> pn‐Heterodiodes comprising the wide bandgap semiconducting oxide In2O3 and amorphous p‐conducting NiO or ZnCo2O4 are realized. In2O3 is grown at 600 °C and the amorphous p‐type oxides at room temperature by pulsed‐laser deposition. Highest rectification of about four orders of magnitude is observed for structures with Mg‐doped In2O3 layers having lower carrier density than undoped layers. The p‐ZnCo2O4/n‐In2O3 diodes do not show degradation at elevated temperatures of 150 °C, whereas the p‐NiO/n‐In2O3 diodes degrade irreversibly for T > 100 °C. Thermal admittance spectroscopy revealed shallow defect levels in the In2O3 layer with activation energy of about 12 and 250 meV, respectively.